Tissue-specific expression of the SARS-CoV-2 receptor, angiotensin-converting enzyme 2, in mouse models of chronic kidney disease - Shunichiro Tsukamoto (Nature Portfolio, 2021)
Abstract Elevated angiotensin-converting enzyme 2 (ACE2) expression in organs that are potential targets of severe acute respiratory syndrome coronavirus 2 may increase the risk of coronavirus disease 2019 (COVID-19) infection. Previous reports show that ACE2 alter its tissue-specific expression patterns under various pathological conditions, including renal diseases. Here, we examined changes in pulmonary ACE2 expression in two mouse chronic kidney disease (CKD) models: adenine-induced (adenine mice) and aristolochic acid-induced (AA mice). We also investigated changes in pulmonary ACE2 expression due to renin–angiotensin system (RAS) blocker (olmesartan) treatment in these mice. Adenine mice showed significant renal functional decline and elevated blood pressure, compared with controls. AA mice also showed significant renal functional decline, compared with vehicles; blood pressure did not differ between groups. Renal ACE2 expression was significantly reduced in adenine mice and AA mice; pulmonary expression was unaffected. Olmesartan attenuated urinary albumin excretion in adenine mice, but did not affect renal or pulmonary ACE2 expression levels. The results suggest that the risk of COVID-19 infection may not be elevated in patients with CKD because of their stable pulmonary ACE2 expression. Moreover, RAS blockers can be used safely in treatment of COVID-19 patients with CKD.